2015
DOI: 10.1097/icu.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

The role of lens extraction in the current management of primary angle-closure glaucoma

Abstract: Good outcomes in terms of long-term IOP control have been found following lens extraction for PACG. Lens extraction should be considered in patients with PACG, especially with hyperopia, or a thick and anteriorly vaulted lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…Patients with acute attacks of angle closure (a rare presentation of the disease) were excluded in our trial, and thus studies evaluating lens extraction for acute attacks are not comparable 2526 A review conducted by Trikha et al 8 has suggested that lens extraction for PACG is associated with better IOP control, reduced complication rates and reduced need for IOP-controlling medications compared to other relevant treatments. These findings are in keeping with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute attacks of angle closure (a rare presentation of the disease) were excluded in our trial, and thus studies evaluating lens extraction for acute attacks are not comparable 2526 A review conducted by Trikha et al 8 has suggested that lens extraction for PACG is associated with better IOP control, reduced complication rates and reduced need for IOP-controlling medications compared to other relevant treatments. These findings are in keeping with ours.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication in Medscape by Laurie Barclay, M.D. "Clear-Lens Extraction May Be Best for Primary Glaucoma" pointed out that clear lens extraction was more effective and more cost-effective than LPI [8] IOP spikes post-op while CE eyes achieved lower IOP and deeper ACD [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…[27] This explains the benefit of lens extraction in PAC eyes without permanent trabecular damage with repeated episodes of irido-corneal contact. [28,29] Newer imaging techniques have now shifted the focus on the lens vault rather than axial lens thickness. [29,30] The importance of iris configuration has been renewed with the use of modern angle imaging systems with due recognition of varied course of eyes with plateau iris after LPI.…”
Section: Discussionmentioning
confidence: 99%